Employee Performance Analysis in the Use of the SIAP GAKKUM Application at the Environmental and Forestry Law Enforcement and Security Center in the Sulawesi Region - Jamaluddin Jamaluddin; Muh. Andrawan Pratama Putra Ratno; Suprianto Suprianto; Sitti Hardiyanti Arhas (Journal of Social Science and Economics (JOSSE), 2025)
This study aims to measure the performance of employees in using the mail application information system (SIAP GAKKUM) at the Environmental and Forestry Law Enforcement and Security Center in the Sulawesi region. Because this research is qualitative, the data collection techniques used to achieve the research objectives are observation, interviews, and documentation. There are five informants, namely four employees and the center's head. The results of the study stated that 1) The performance of employees in the use of the correspondence application information system (SIAP GAKKUM) is good, but it is still necessary to hold a training seminar for each employee so that they are more fluent in using the application; 2) There are still many employees who are still not fluent in using or operating the correspondence application information system (SIAP GAKKUM) so that sometimes they have to be assisted by the admin of the correspondence section; and 3) The role of superiors is no less critical in supervising employee performance when using the correspondence application information system (SIAP GAKKUM) because when superiors provide encouragement or motivation, they can use the application better.